Pergeseran Makna Al-Maghdub dan Ad-Dhallin dalam Qs. Al-Fatihah Ayat 7 : (Studi Analisis Semiotika Roland Barthes) - Muchammad Faz Tazakka (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
his article analyzes the semantic shifts of al-Maghdub (those who incur wrath) and ad-Dhallin (those who go astray) in QS. Al-Fatihah: 7 using Roland Barthes’ semiotics framework. The study aims to uncover the layers of meaning—literal (denotation), symbolic (connotation), and mythological—embedded in these terms. Employing a descriptive-analytical method and library research, the study reveals that classical exegesis often associates al-Maghdub with the Jews and ad-Dhallin with Christians. However, Barthes’ semiotic analysis suggests a broader, universal interpretation. Al-Maghdub represents those who consciously reject the truth, while ad-Dhallin refers to individuals who deviate from the right path due to ignorance or external influences. At the mythological level, these terms transcend specific religious identities, reflecting universal moral categories relevant to the spiritual and ethical challenges of modern humanity.